Disease severity and clinical outcomes of community-acquired pneumonia caused by non-influenza respiratory viruses in adults: a multicentre prospective registry study from the CAP-China Network. Issue 2 (1st August 2019) - Zhou, Fei; Wang, Yimin; Liu, Yingmei; Liu, Xuedong; Gu, Li; Zhang, Xiaoju; Pu, Zenghui; Yang, Guoru; Liu, Bo; Nie, Qingrong; Xue, Bing; Feng, Jing; et al.
Although broad knowledge of influenza viral pneumonia has been established, the significance of non-influenza respiratory viruses in community-acquired pneumonia (CAP) and their impact on clinical outcomes remains unclear, especially in the non-immunocompromised adult population. Hospitalised immunocompetent patients with CAP were prospectively recruited from 34 hospitals in mainland China. Respiratory viruses were detected by molecular methods. Comparisons were conducted between influenza and non-influenza viral infection groups. In total, 915 out of 2336 adult patients with viral infection were enrolled in the analysis, with influenza virus (28.4%) the most frequently detected virus, followed by respiratory syncytial virus (3.6%), adenovirus (3.3%), human coronavirus (3.0%), parainfluenza virus (2.2%), human rhinovirus (1.8%) and human metapneumovirus (1.5%). Non-influenza viral infections accounted for 27.4% of viral pneumonia. Consolidation was more frequently observed in patients with adenovirus infection. The occurrence of complications such as sepsis (40.1% versus 39.6%; p=0.890) and hypoxaemia (40.1% versus 37.2%; p=0.449) during hospitalisation in the influenza viral infection group did not differ from that of the non-influenza viral infection group. Compared with influenza virus infection, the multivariable adjusted odds ratios of CURB-65 (confusion, urea >7 mmol·L −1, respiratory rate ≥30 breaths·min −1, blood pressure <90 mmHg (systolic) or ≤60 mmHg (diastolic), age ≥65 years) ≥3, arterial oxygen tension/inspiratory oxygen fraction <200 mmHg, and occurrence of sepsis and hypoxaemia for non-influenza respiratory virus infection were 0.87 (95% CI 0.26–2.84), 0.72 (95% CI 0.26–1.98), 1.00 (95% CI 0.63–1.58) and 1.05 (95% CI 0.66–1.65), respectively. The hazard ratio of 90-day mortality was 0.51 (95% CI 0.13–1.91). The high incidence of complications in non-influenza viral pneumonia and similar impact of non-influenza respiratory viruses relative to influenza virus on disease severity and outcomes suggest more attention should be given to CAP caused by non-influenza respiratory viruses. The high incidence of complications in non-influenza viral pneumonia and similar impact of non-influenza viruses relative to influenza virus on disease severity and outcomes suggest more attention should be given to CAP caused by non-influenza viruses http://bit.ly/2vRTvFK